Optimizing leaf nutrient status, growth, and yield parameters in high-density apple orchards (cv. Super chief) via integrated drip irrigation and fertigation techniques - Kapil Sharma; J.C. Sharma; Sunny Sharma; Nitin Sharma; Rohit Sharma; Ananthakrishnan S; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd_Allah (Heliyon, 2024)
Nutrients and water are important ecophysiological components for apples' development and productivity. The combination of high-density plantation, drip irrigation, and weekly fertigation not only conserves irrigation water, but also reduces cultivation costs compared to conventional methods. Leaf nutrient analysis provides insight into nutrient levels and assists in determining irrigation and fertigation schedules. We conducted the current research over two years (2021–22 and 2022–23) to evaluate different drip-fertigation effects on leaf nutrient status, vegetative growth, and yield of high-density apples. The experimental study employed a factorial randomised block design, replicating 16 different treatment combinations three times each. Each replication consisted of three plants, and the treatments included four irrigation levels (100 %, 80 %, 60 %, and control) and four fertigation levels (absolute control, 100 %, 75 %, and 50 % of the recommended NPK dosage). Analysis of the leaves indicated that IR1 (Drip irrigation at 100 % ETc) showed notably higher levels of nitrogen at (3.06 %), phosphorus at (0.48 %) and potassium at (2.07 %) compared to other treatments. Regarding fertigation levels, FN1 [100 % (AD) NPK] showed the highest nitrogen (3.12 %), phosphorus (0.50 %), and potassium (2.09 %) content. Parameters related to vegetative growth, including tree height, plant spread in both east-west (EW) and north-south (NS) directions, trunk girth, annual extension growth, and leaf area showed significant increases with higher irrigation and fertigation levels, surpassing conventional irrigation (IR4) by 6.17 percent, 7.78 percent (EW), 8.62 percent (NS), 10.49 percent, 4.53 percent and 1.96 percent, respectively. Among fertigation, FN1- 100 % AD (NPK) registered a maximum increase in growth parameters. Our analysis demonstrated that combining irrigation and fertigation improved leaf nutrient status and vegetative growth characteristics, which are critical determinants of fruit yield.